Sexual practices in a broad cross-sectional sample of Sydney gay men - Paul van deVen; Susan Kippax; June Crawford; Judy French; Garrett Prestage; Andrew Grulich; John Kaldor; Paul Kinder (Elsevier, 1997)
Abstract: The aim of this study was to provide current data on the sexual practices in a broad cross-sectional sample of gay and homosexually active men in Sydney. Anonymous, short questionnaires were completed by 1611 gay men recruited at the 1996 Gay and Lesbian Mardi Gras Fair Day or at one of six venues (including two sexual health centres) across the metropolitan area during the following week. The sample was diverse, but the men tended to be of Anglo-Australian background, well educated, professionally employed, attached to gay community and gay identified. They mainly had sex with other men rather than with men and women. Most (86.0 per cent) had been tested for human immunodeficiency virus. Excluding 241 men recruited in sexual health centres, 11.2 per cent were HIV-positive and 73.4 per cent were negative. Where it occurred in regular relationships, unprotected anal intercourse was usually between seroconcordant partners (78.5 per cent). Unprotected anal intercourse between discordant or noncon-cordant regular partners was much less common, and in about half the cases involved withdrawal prior to ejaculation exclusively rather than ejaculation inside. Almost 12 per cent of the men had at least 'occasionally' engaged in unprotected anal intercourse with a casual partner in the previous six months, with approximately half of these men having adopted a withdrawal strategy on every occasion. We conclude that short surveys can provide valuable and timely data on sexual practices in a broad cross-sectional sample of gay and homosexually active men. Key messages for those involved in gay men's education are the high rates of unprotected anal intercourse between casual partners and the extensive practice of withdrawal.